Simulation of a single phase inter-tie grid connected inverter / Izelein Hajar Zulkafree - Zulkafree, Izelein Hajar (2006)
This thesis presented a report on the performance of the grid connected inter-tie inverter. The information reported in this thesis includes the detailed analysis on the simulation progress based on the bridge topology using the PSIM simulation software. The system utilizes a single phase grid-connected inverter which can draw power from a solar energy input to be interfaced with 240V and 50Hz frequency as indicated in Malaysia.